Efficient Asymmetric Biomimetic Aldol Reaction of Glycinates and Trifluoromethyl Ketones by Carbonyl Catalysis. Issue 37 (13th July 2021) - Cheng, Aolin; Zhang, Liangliang; Zhou, Qinghai; Liu, Tao; Cao, Jing; Zhao, Guoqing; Zhang, Kun; Song, Guanshui; Zhao, Baoguo
Abstract: The direct asymmetric aldol reaction of glycinates represents an intriguing and straightforward strategy to make biologically significant chiral β‐hydroxy‐α‐amino‐acid derivatives. But it is not easy to realize the transformation due to the disruption of the reactive NH2 group of glycinates. Inspired by the enzymatic aldol reaction of glycine, we successfully developed an asymmetric aldol reaction of glycinate 5 and trifluoromethyl ketones 4 with 0.1–0.0033 mol % of chiral N ‐methyl pyridoxal 7 a as the catalyst, producing chiral β‐trifluoromethyl‐β‐hydroxy‐α‐amino‐acid esters 6 in 55–82 % yields (for the syn ‐diastereomers) with up to >20:1 dr and 99 % ee under very mild conditions. The reaction proceeds via a catalytic cycle similar to the enzymatic aldol reaction of glycine. Pyridoxal catalyst 7 a activates both reactants at the same time and brings them together in a specific spatial orientation, accounting for the high efficiency as well as excellent diastereo‐ and enantioselectivities. Abstract : An efficient biomimetic aldol reaction of glycinate and trifluoromethyl ketones was developed with 0.1–0.0033 mol % of chiral pyridoxal 7 a as the catalyst, producing β‐hydroxy‐α‐amino‐acid esters 6 in 55–82 % yields with excellent diastereo‐ and enantioselectivities (up to >20:1 dr and 99 % ee ) without protection of the active NH2 group. The reaction proceeds via a bifunctional‐catalysis pathway similar to the enzymatic aldol reaction of glycine.